Multicenter validation study of pathologic response and tumor thickness at the tumor‐normal liver interface as independent predictors of disease‐free survival after preoperative chemotherapy and surgery for colorectal liver metastases. Issue 15 (23rd April 2013) - Brouquet, Antoine; Zimmitti, Giuseppe; Kopetz, Scott; Stift, Judith; Julié, Catherine; Lemaistre, Anne‐Isabelle; Agarwal, Atin; Patel, Viren; Benoist, Stephane; Nordlinger, Bernard; Gandini, Alessandro; Rivoire, Michel; et al.
Abstract : BACKGROUND: To validate pathologic markers of response to preoperative chemotherapy as predictors of disease‐free survival (DFS) after resection of colorectal liver metastases (CLM). METHODS: One hundred seventy‐one patients who underwent resection of CLM after preoperative chemotherapy at 4 centers were studied. Pathologic response—defined as the proportion of tumor cells remaining (complete, 0%; major, <50%; minor, ≥50%) and tumor thickness at the tumor‐normal liver interface (TNI) (<0.5 mm, 0.5 to <5 mm, ≥5 mm)—was assessed by a central pathology reviewer and local pathologists. RESULTS: Pathologic response was complete in 8% of patients, major in 49% of patients, and minor in 43% of patients. Tumor thickness at the TNI was <0.5 mm in 21% of patients, 0.5 to <5 mm in 56% of patients, and ≥5 mm in 23% of patients. On multivariate analyses, using either pathologic response or tumor thickness at TNI, pathologic response ( P  = .002, .009), tumor thickness at TNI ( P  = 0.015, <.001), duration of preoperative chemotherapy ( P  = .028, .043), number of CLM ( P  = .038, . 037), and margin ( P  = .011, .016) were associated with DFS. In a multivariate analysis using both parameters, tumor thickness at TNI ( P  = .004, .015), duration of preoperative chemotherapy ( P  = .025), number of nodules ( P  = .027), and margin ( P  = .014) were associated with DFS. Tumor size by pathology examination was the predictor of pathologic response. Predictors of tumor thickness at the TNI were tumor size and chemotherapy regimen. There was near perfect agreement for pathologic response (κ = .82) and substantial agreement (κ = .76) for tumor thickness between the central reviewer and local pathologists. CONCLUSIONS: Pathologic response and tumor thickness at the TNI are valid predictors of DFS after preoperative chemotherapy and surgery for CLM. Cancer 2013 ;119:2778–2788. © 2013 American Cancer Society. Abstract : Pathologic response and tumor thickness at the tumor‐normal interface are reproducible criteria that may be used in routine clinical practice and are new end points for the assessment of biomarkers of chemotherapy response in colorectal liver metastases.